Fermion masses, neutrino mixing and Higgs-mediated flavor violation in 3HDM with S 3 permutation symmetry - K. S. Babu; Yongcheng Wu; Shiyuan Xu (Journal of High Energy Physics)
Abstract The Yukawa and scalar sectors of a general S 3-symmetric three-Higgs doublet model (3HDM) are investigated. The Yukawa interactions are constructed in an S 3-invariant way, while the scalar potential contains S 3 soft-breaking terms. Global fits to the quark/lepton masses and CKM/PMNS matrices are performed. Excellent fits to all fermion mass and mixing parameters are obtained. Both normal ordering and inverted ordering of neutrino masses are found to be admissible within the framework, with a prediction for the CP-violation phase, δ CP ≃ 120°. The fit results in the Yukawa sector are further investigated, together with the scalar sector, imposing constraints from Higgs-mediated neutral meson mixing and neutron electric dipole moment (EDM). We explore the lowest allowed mass of the heavy Higgs bosons, consistent with these constraints, and find it to be about 17 TeV. The corresponding neutron EDM is around 1.7 × 10 −27 e-cm, which is within reach of proposed experiments. It is found that the constraints from the K-meson system dominate, while those from the D meson system are marginal.